DESAIN DAN IMPLEMTASI MONITORING INFRATRUKTUR PRANGKAT JARINGAN MENGGUNAKAN GRAFANA DN PROMETHEUS - Saputra, Muhamad Doni (JATISI, 2025)
In increasingly complex computing environments, particularly when multiple servers require simultaneous monitoring, the presence of a monitoring system becomes crucial to ensure IT infrastructure performance and availability. This study aims to address this need by developing an effective, efficient, and real-time monitoring system using open-source software such as Grafana, Prometheus, InfluxDB, and Telegraf. To solve this problem, a structured system development approach adaptable to infrastructure requirements was necessary. The method employed was the Network Development Life Cycle (NDLC) model, consisting of three main stages: analysis, design, and prototype simulation. The developed system was designed to monitor server CPU, memory, and hard disk conditions, equipped with automatic notification features via Telegram when device anomalies are detected. Test results demonstrated the system's capability to provide rapid response to critical conditions with an average notification delivery time of three seconds. Furthermore, performance data visualization was presented interactively through Grafana dashboards, facilitating comprehensive monitoring by administrators. These findings prove that integrating open-source monitoring components can enhance IT infrastructure management efficiency and holds potential for further development on a larger scale.